Application of planter force measurement in evaluation of soccer shoes - Hong, Y.; Dewei, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Normal soccer shoes are manufactured using homogenous material for midsole. Soccer game requires the players to tackle the soccer ball as quickly as possible. It was thought that a dual density material design of the midsole may provide better control to the foot. To study this question, we developed prototype soccer shoes with two different midsole designs. One was made up by homogeneous EVA material (Shore A 95) and the other (S2) was made up by the same material except for the forefoot area where a relatively soft EVA material (Shore A 85) was used. Both shoes have similar structure and material in all other aspects including the studs. The purpose of this study was to compare the plantar force generated during 30-m sprint wearing soccer shoes with homogeneous and dual density midsole designs.